Integrasi Konsep Anak Angkat dalam Pembagian Waris di Indonesia: Analisis Yuridis terhadap Dinamika Hukum Positif - Yassin, Iqbal; Sanjaya, Prasetya (Lex Stricta : Jurnal Ilmu Hukum, 2025)
This study investigates the complexities associated with the reassessment of child adoption laws and the framework governing the distribution of inheritance to adopted children, as described by Islamic law and civil law. The methodological approach used in this investigation is normative jurisprudence, combining a thorough examination of the library to identify a strong legal basis in the form of legal dogma or doctrine that can effectively address questions related to the subject matter at hand. Furthermore, the analysis covers relevant legal statutes concerning child adoption and inheritance asset allocation, in line with the provisions of Islamic law and civil law. The findings of this study indicate that, under Islamic law, the process of child adoption does not alter the existing legal relationship between the adopted child and the adoptive parents, either in terms of lineage or maternal relationship; rather, the judicial determination of adoption equates the status of the adopted child with that of a biological child, thereby establishing equality in the legal consequences regarding the distribution of inheritance, as articulated in Article 852 of the Civil Code. In the context of Islamic law, the rights of adopted children are a significant consideration, whereby the inheritance rights of these children can be facilitated through compulsory inheritance, as stated in Article 209 of the Compilation of Islamic Law (KHI)